2010
DOI: 10.1002/ptr.3338
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids inhibit angiogenic cytokine production by human glioma cells

Abstract: VEGF and TGF-β1 are cytokines that stimulate tissue invasion and angiogenesis. These factors are considered as molecular targets for the therapy of glioblastoma. Bevacizumab, a recombinant humanized monoclonal antibody developed against VEGF, inhibits endothelial cell proliferation and vessel formation. Flavonoids obtained from Dimorphandra mollis and Croton betulaster have been described as proliferation inhibitors of a human glioblastoma derived cell line. VEGF and TGF-β1 levels were dosed by ELISA in a GL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
0
36
0
2
Order By: Relevance
“…Recent studies found that casticin can inhibit intercellular adhesion molecule-1 (ICAM-1) expression and eosinophil migration in lung epithelial cells (Koh et al, 2011). Casticin can also induce apoptosis of cancer cells, including glioma cells, human lung cancer cells, cervical cancer cells, gastric cancer cells, and hepatocellular carcinomas (Freitas et al, 2011;Koh et al, 2011;Zhou et al, 2013). However, the anti-inflammatory effect of casticin is not fully understood.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies found that casticin can inhibit intercellular adhesion molecule-1 (ICAM-1) expression and eosinophil migration in lung epithelial cells (Koh et al, 2011). Casticin can also induce apoptosis of cancer cells, including glioma cells, human lung cancer cells, cervical cancer cells, gastric cancer cells, and hepatocellular carcinomas (Freitas et al, 2011;Koh et al, 2011;Zhou et al, 2013). However, the anti-inflammatory effect of casticin is not fully understood.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, luteolin inhibited the proliferation of a human myeloid leukaemia cell line and a human colon carcinoma cell lines by inducing apoptosis (Ko et al, 2002;Imai et al, 2009). Moreover, vitexicarpin showed the ability to reduce the production of the angiogenic Transforming Growth Factor (TGF)-b-1 by a human glioblastoma-derived cell line, emphazing its potential activity as angiogenic factors inhibitor (Freitas et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…As shown in Figure 1, accumulated data indicate that casticin was isolated from many plant species such as, namely Vitex agnus castus (Choudhary et al, 2009;Mesaik et al, 2009;Webster et al, 2011;Righeschi et al, 2012;Hogner et al, 2013), Daphne genkwa (Xie et al, 2011), Achillea millefolium (Haidara et al, 2006;Csupor-Loffler et al, 2009), Ficus microcarpa , Vitex rotundifolia (Ono et al, 2002;Hu et al, 2007b;Shen et al, 2009;Ye et al, 2010;Koh et al, 2011), Fructus viticis (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011b;Yang et al, 2011;Zeng et al, 2012;Zhou et al, 2013a), Vitex negundo (Diaz et al, 2003;Kunwar et al, 2010;Velpandian et al, 2013), Crataegus pinnatifida (Kao et al, 2005), Pavetta crassipes (Mali and Dhake, 2011), Nelsonia canescens, Butea frondosa Koen , Dalbergia odorifera (Mali and Dhake, 2011), Bryonia laciniosa (Aggarwal et al, 2011), Citrus unshu (Mali and Dhake, 2011;Nagoor et al, 2011), Centipeda minima (Mali and Dhake, 2011), Clausena excavate (Manosroi et al, 2005), Croton betulaster (de Sampaio e Spohr et al, 2010;Freitas et al, 2011), Dimorphandra mollis (Freitas et al, 2011), Artemisia abrotanum L. (Hernandez et al, 1999), Artemisia annua L …”
Section: Natural Sources Of Casticinmentioning
confidence: 99%
“…Casticin induced early or late apoptosis in a dose dependent manner. Sub-G1 accumulation is usually considered as an apoptotic death profile, this evidence is in sync with mode of cell death and characterized by a set of physiological phenomena, including mitotic catastrophe (Ono et al, 2002;Hu et al, 2007a;Hu et al, 2007b;Shen et al, 2009;Guan et al, 2010;Ye et al, 2010;Chen et al, 2011a;Koh et al, 2011;Zeng et al, 2012;Zhou et al, 2013a) Fructus viticis Chaste tree Mang Jing Zi Fruit Anticancer, inflammation (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011a;Zeng et al, 2012;Zhou et al, 2013a) Dimorphandra mollis --------Seeds vascular disorders; hypertension (Freitas et al, 2011) Artemisia abrotanum L.…”
Section: 9049 Molecular Mechanisms Of Casticin Action: An Update On mentioning
confidence: 99%
See 1 more Smart Citation